DIRECT APPLICATION OF THE CONSTITUTIONAL NORM AS A GUARANTEE OF THE PROHIBITION OF ABUSE OF RIGHT - Barseghyan, Sose (State and Law, 2022)
The relevance of the article is the development of the institution of abuse of right and the need to choose effective means for protecting rights.The article presents the institution of abuse of right, in the case of the proper implementation of which the institution having a constitutional basis can itself become a tool for the protection of rights, and especially in cases where the legislative mechanisms for the protection of rights are weak.
Keywords: abuse of the right; violation of the right; the purpose of the right